(3SajfI fhMs - (3YeQ Hf CMeO GdMdHj GdTeGYs; (3Jbi GdOjf GdaGSis
(3ChdgG (B:s
(3JGQN ecI GdeTQaI s
(3hbO LeYgG GdeDda ef cJH TJi aj GdJhGQjN CKfGA eLGhQJg GdKGfjI HecI GdeTQaI SfI (B927 (3g`s
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B82 s
Keywords: (3GdJGQjNs